The European race of Gremmeniella abietina hosts a single species of Gammapartitivirus showing a global distribution and possible recombinant events in its history - Botella, Leticia; Tuomivirta, Tero T; Hantula, Jarkko; Diez, Julio J; Jankovsky, Libor (Fungal biology, 2015)
The population genetics of the family Partitiviridae was studied within the European race of the conifer pathogen Gremmeniella abietina. One hundred sixty-two isolates were collected from different countries, including Canada, the Czech Republic, Finland, Italy, Montenegro, Serbia, Spain, Switzerland, Turkey and the United States. A unique species of G. abietina RNA virus-MS1 (GaRV-MS1) appears to occur indistinctly in G. abietina biotypes A and B, without a particular geographical distribution pattern. Forty-six isolates were shown to host GaRV-MS1 according to direct specific RT-PCR screening, and the virus was more common in biotype A than B. Phylogenetic analysis based on 46 partial coat protein (CP) cDNA sequences divided the GaRV-MS1 population into two closely related clades, while RNA-dependent RNA polymerase (RdRp) sequences revealed only one clade. The evolution of the virus appears to mainly occur through purifying selection but also through recombination. Recombination events were detected within alignments of the three complete CP and RdRp sequences of GaRV-MS1. This is the first time that recombination events have been directly identified in fungal partitiviruses and in G. abietina in particular. The results suggest that the population dynamics of GaRV-MS1 do not have a direct impact on the genetic structure of its host, G. abietina, though they might have had an innocuous ancestral relationship.
Keywords: United States; sekvenční analýza DNA; Recombination, Genetic; Kanada; Reverse Transcriptase Polymerase Chain Reaction; sekvenční homologie; Ascomycota; Canada; Sequence Analysis, DNA; molekulární sekvence - údaje; RNA virová; Sequence Homology; Evropa; shluková analýza; polymerázová řetězová reakce s reverzní transkripcí; Cluster Analysis; genotyp; Phylogeny; RNA Viruses; fylogeneze; molekulární evoluce; rekombinace genetická; Genotype; RNA-viry; Molecular Sequence Data; Europe; RNA, Viral; Spojené státy americké; Evolution, Molecular